System level optimization of series hybrid electric vehicle through plug-in charging feature using ADVISOR - Hassan, Zain ul; Ahmad, Naseer; Sohaib, Muhammad (Institute of Advanced Engineering and Science, 2025)
This research addresses the optimization of series hybrid electric vehicles (SHEVs) to enhance sustainable transportation by integrating a plug-in charging feature. The primary objective is to extend the range and improve battery management. Using MATLAB Simulink and the advanced vehicle simulator (ADVISOR), three SHEVs scenarios were simulated under the urban dynamometer driving system (UDDS) cycle. The study maintains constant parameters for the fuel converter and generator while optimizing the battery and motor controller. Compared to conventional hybrid electric vehicles (HEVs), this optimized SHEVs demonstrates a 17% improvement in battery thermal management and a 13.5% reduction in power losses. Additionally, the plug-in series hybrid electric vehicle (P-SHEVs) configuration shows a 5.26% increase in power output and a 35.71% improvement in the state of charge (SOC) over standard SHEVs configurations. The P-SHEVs design also achieves a 12.20% increase in the UDDS single-cycle range and an 11.5% reduction in fuel consumption. The integration of the electric vehicle (EV) charging feature further enhances the SHEVs, resulting in an 8.33% boost in motor power input and a 6.35% improvement in motor temperature profile, reaching a peak enhancement of 50% (18 kW). It contributes to the field by demonstrating the effectiveness of optimized configurations and the integration of a plug-in charging feature in SHEVs, thereby advancing the capacity of these vehicles to promote greener transportation solutions.